Preparation and characterization of SnO2 doped TiO2 nanoparticles: Effect of phase changes on the photocatalytic and catalytic activity - Hassan, Shawky M. (Elsevier, 2019)
The effects of phase changes on the photocatalytic and catalytic activities of SnO2/TiO2 nanoparticles prepared via surfactant-assisted sol-gel method were investigated. The as-prepared SnO2/TiO2 was calcined at 400 , 500 , 600 , and 700 C. The prepared samples were studied by XRD, TEM, SEM, FTIR, BET, UV-vis diffuse reflection spectroscopy (DRS) and Photoluminescence (PL) spectra. The results showed that the crystallite size and anatase-to-rutile phase transformation increase greatly with increasing the calcination temperature. The transformation of anatase to rutile phase was found to be between 400 and 600 C, and then the anatase completely transformed to rutile phase at 700 C. Also, the specific surface area and pore volume decrease, whereas the mean pore size increases with increasing the calcination temperature. The effect of calcination temperature on the catalytic activity of the samples was tested by different applications: photodegradation of Methylene Blue (MB), Rhodamine B (RhB) dyes and phenol and synthesis of xanthene (14-phenyl-14H-dibenzo [a,j]xanthene). The mineralization of MB and RhB has been confirmed by chemical oxygen demand (COD) measurements. The results showed that the SnO2/TiO2 nanoparticles calcined at 500 C exhibit the highest photocatalytic and catalytic activities